Resting Metabolic Rate and Lung Function in Wild Offshore Common Bottlenose Dolphins, Tursiops truncatus, Near Bermuda - Fahlman, Andreas; McHugh, Katherine; Allen, Jason; Barleycorn, Aaron; Allen, Austin; Sweeney, Jay; Stone, Rae; Faulkner Trainor, Robyn; Bedford, Guy; Moore, Michael J.; Jensen, Frants H.; Wells, Randall (Frontiers in Physiology, 2018)
Diving mammals have evolved a suite of physiological adaptations to manage respiratory gases during extended breath-hold dives. To test the hypothesis that offshore bottlenose dolphins have evolved physiological adaptations to improve their ability for extended deep dives and as protection for lung barotrauma, we investigated the lung function and respiratory physiology of 4 wild common bottlenose dolphins (Tursiops truncatus) near the island of Bermuda. We measured blood haematocrit (Hct, %), resting metabolic rate (RMR, l O2 min-1), tidal volume (VT, l), respiratory frequency (fR, breaths min-1), respiratory flow (l min-1), and dynamic lung compliance (CL, l cmH2O-1) in air and in water, and compared measurements with published results from coastal, shallow-diving dolphins. We found that offshore dolphins had greater Hct (56±2%) compared to shallow-diving bottlenose dolphins (range: 30-49%), thus resulting in a greater O2 storage capacity and longer aerobic diving duration. Contrary to our hypothesis, the specific CL (sCL, 0.30 ± 0.12 cmH2O-1) was not different between populations. Neither the mass-specific RMR (3.0±1.7 ml O2 min-1 kg-1), nor VT (23.0 ± 3.7 ml kg-1) were different from coastal ecotype bottlenose dolphins, both in the wild and under managed care, suggesting that deep-diving dolphins do not have metabolic or respiratory adaptations that differs from the shallow-diving ecotypes. The lack of respiratory adaptations for deep diving further support the recently developed hypothesis that gas management in cetaceans is not entirely passive but governed by alteration in the ventilation-perfusion matching, which allows for selective gas exchange to protect against diving related problems such as decompression sickness.